Paradoxical effects of JZL184, an inhibitor of monoacylglycerol lipase, on bone remodelling in healthy and cancer-bearing mice - Marino, Silvia (EBioMedicine, 2019)
BACKGROUND: Cancer-associated bone disease is a serious complication in bone sarcomas and metastatic carcinomas of breast and prostate origin. Monoacylglycerol lipase (MAGL) is an enzyme of the endocannabinoid system, and is responsible for the degradation of the most abundant endocannabinoid in bone, 2-arachidonoyl glycerol (2AG). METHODS: The effects of the verified MAGL inhibitor on bone remodelling were assessed in healthy mice and in mouse models of bone disease caused by prostate and breast cancers and osteosarcoma. FINDINGS: JZL184 reduced osteolytic bone metastasis in mouse models of breast and prostate cancers, and inhibited skeletal tumour growth, metastasis and the formation of ectopic bone in models of osteosarcoma. Additionally, JZL184 suppressed cachexia and prolonged survival in mice injected with metastatic osteosarcoma and osteotropic cancer cells. Functional and histological analysis revealed that the osteoprotective action of JZL184 in cancer models is predominately due to inhibition of tumour growth and metastasis. In the absence of cancer, however, exposure to JZL184 exerts a paradoxical reduction of bone volume via an effect that is mediated by both Cnr1 and Cnr2 cannabinoid receptors. INTERPRETATION: MAGL inhibitors such as JZL184, or its novel analogues, may be of value in the treatment of bone disease caused by primary bone cancer and bone metastasis, however, activation of the skeletal endocannabinoid system may limit their usefulness as osteoprotective agents.